Cytogenetic and molecular study of 370 infertile men in South India highlighting the importance of copy number variations by multiplex ligation‐dependent probe amplification - Dutta, Usha R.; Suttur, Malini S.; Venugopal, Vineeth S.; Posanapally, Laxmi Priyanka; Gopalasetty, Sravani; Talwar, Sangamesh; Anand, Suhana; Billapati, Sushmita; Jesudasan, Rachel A.; Dalal, Ashwin (Andrologia, 2020)
Male infertility is a common and severe problem affecting 7% of population. The main objective of this study is to identify the chromosomal abnormalities, Y microdeletions in infertile men and also to access the frequency of abnormal sperm count. Based on the sperm count and viability, the infertile men were grouped as Azoospermia, Asthenospermia, Oligospermia and the remaining as Idiopathic infertility. A total of 370 infertile men and 60 normal control men were recruited. Chromosomal abnormalities were identified in 3 men (3/370). The prevalence of Y microdeletions in the infertile group is 8/370 in the Azoospermia factor (AZF) region with four AZFc deletion/duplication, two AZFa deletion, one AZF b & AZFc deletion and one case of total AZF a, AZFb & AZFc deletion. However, only five cases of Y microdeletions were identified by Multiplex PCR but an additional three cases by MLPA (Multiplex ligation‐dependent probe amplification). Fluorescence in situ hybridisation also confirmed the deletions. Here, we performed MLPA post‐multiplex PCR, and our study revealed good yield of the Y microdeletion identification. The partial duplications which are difficult to be identified can now be easily identified by MLPA, and hence, we recommend MLPA as the choice of investigation compared to multiplex PCR for infertile men.